Trypsin inhibitor LH011 inhibited DSS-induced mice colitis via alleviating inflammation and oxidative stress - Jia, Zhenmao; Wang, Panxia; Xu, Yuansheng; Feng, Guodong; Wang, Quan; He, Xiangjun; Song, Yan; Liu, Peiqing; Chen, Jianwen (Frontiers in Pharmacology, 2022)
Background: Ulcerative colitis (UC) is one type of inflammatory bowel disease, characterized by inflammation with infiltration and activation of macrophages in colonic tissue. LH011 is a trypsin inhibitor with potential anti-inflammatory effect. Purpose: Here, we aim to assay the effects of LH011 on UC and further investigate the potential mechanisms in vitro and in vivo. Methods: Dextran sulfate sodium (DSS, 3.5%, w/v) was used to induce UC, and lipopolysaccharide (LPS) was used to induce inflammation in RAW 264.7 cells. LH011 was administrated to mice in vivo or to RAW 264.7 cells in vitro at different concentrations. The cytokines (IL-1β, IL-6, and TNF-α) and the changes of NF-κB and Nrf2 pathways were detected. Results: The results showed that LH011 improved DSS-induced mice colitis, including loss of weight, disease activity index (DAI), and colonic pathological damage. In addition, LH011 inhibited the expressions of IL-1β, IL-6, and TNF-α and strengthened the anti-oxidative capacity. Mechanically, LH011 downregulated the nuclear localization of NF-κB p65 and upregulated the protein expression of Nrf2. Conclusion: These results demonstrated that LH011 alleviated inflammation and oxidative stress during UC by inhibiting TLR4/NF-κB and activating Nrf2/Keap1/HO-1 signaling pathways.